(untitled) - Lethbridge, Timothy C. (Boston, 2005)
This widely used book teaches practical object-oriented software engineering with the key real world tools UML, design patterns and Java. This step-by-step approach allows the reader to address complex and changing problems with practical and state-of-the-art solutions.
Ngôn ngữ mô hình hóa
Keywords: Software engineering,Object-oriented programming (Computer science),Công nghệ phần mềm